CONTROL SYSTEM FUEL OIL SALES IN PT. PATRA ELNUSA RETAIL BRANCH 34-1106 SRENGSENG GAS STATION - Ovy Herlita; Yuce Yuliani, Skom, MMsi (Jurnal Sistem Informasi, 2002)
The presence of retail outlets is needed by consumers who have the vehicles to getfuel. Gas station to get fuel supplies from suppliers that fit well in accordance withthe type of container, and then channeled through the pump machines to serve theamount of spending by consumers.Although prosudernya simple, but often have leaks like a mismatch between therevenue management of the supplier with the actual expenditure transactions.Lupanya caused by officers to record or intention for personal gain. This resulted inconsiderable losses.To anticipate other than the personal approach is also replace records previously donemanually changed automatically to the computer's memory. With the pump I use adigital interface to get transaction reports that have been grouped based on themachine used. This identification is stored on computer memory.